Identifikasi Sesar Gorontalo Dengan Memanfaatkan Data Gravitasi Satelit Resolusi Tinggi - Aina’ul Mardiyah; Ahmad Fauzi Pohan (Universitas Andalas, 2024)
The Gorontalo fault is an active fault and is the main source of earthquakes in Gorontalo Province. A strong and destructive earthquake that has occurred in Gorontalo Province was on November 16, 2008 with a magnitude of 7.4 Mw. As one of the disaster mitigation efforts, a research was conducted to identify the type of Gorontalo fault. Data used from global gravity model plus (GGMplus) as free air anomaly data and shuttle radar topography mission (SRTM2Gravity) as modern terrain correction data that rely on full-scale topographic gravity data. These data are used to calculate the complete Bouguer anomaly data. The complete Bouguer anomaly data was subjected to spectrum analysis to obtain the depth of regional and residual anomalies and to separate regional and residual anomalies using the upward continuation method. On the residual anomaly, second vertical derivative (SVD) analysis was conducted to determine the type of Gorontalo fault. The inversion result of 3D model of gravity anomaly shows Gorontalo fault with medium and low density contrast. Based on the SVD analysis, the Gorontalo fault is a turun fault. This geological structure is considered to be a potential source of natural disasters in the Gorontalo region.